2021
DOI: 10.3390/cancers13040631
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes (PROs) and Health-Related Quality of Life (HR-QoL) in Patients with Ovarian Cancer: What Is Different Compared to Healthy Women?

Abstract: Introduction: The aim of this analysis was to evaluate the health-related quality of life (HR-QoL) in patients with ovarian cancer using a patient-reported outcome (PRO) based questionnaire and to compare it to the healthy female population in Germany and to other ovarian cancer patients worldwide. Additionally, we looked for differences in the HR-QoL with respect to the patients’ ages in our cohort. Methods: The HR-QoL for 155 enrolled patients with ovarian cancer was assessed by the European Organization for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Several surveys found that 43% [ 48 ]-53% [ 17 ] of patients with ovarian cancer complained of fatigue or extreme fatigue. CRF as a long-term side effect in cancer survivors negatively impacts the QoL of patients [ 18 , 49 ]. Home-based exercise, good relationships, and lifestyle interventions can improve QoL and reduce fatigue in patients with ovarian cancer [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys found that 43% [ 48 ]-53% [ 17 ] of patients with ovarian cancer complained of fatigue or extreme fatigue. CRF as a long-term side effect in cancer survivors negatively impacts the QoL of patients [ 18 , 49 ]. Home-based exercise, good relationships, and lifestyle interventions can improve QoL and reduce fatigue in patients with ovarian cancer [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various symptoms are felt impact psychology. Women will experience anxiety, depression, and even lose enthusiasm because they are burdened with their illness, affecting their attitude towards the treatment process (Ebell et al, 2016;Inci et al, 2021;Wulandari, 2018). Social and sexual relationships of ovarian cancer patients will also be disrupted, where women with ovarian cancer do not enjoy intimate relationships with their husbands due to decreased desire to have sex and the pain experienced during sexual intercourse (Ahmed-Lecheheb & Joly, 2016;Fischer et al, 2019;Mayer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%